VD_FINDINFO 127/2012/XMD vom 21. September 2012 - VD Tribunal cantonal (2012)
RESPONSABILITÉ DES ORGANES D'UNE SOCIÉTÉ, DOMMAGE PROPRE, ORGANE DE FAIT, SUBROGATION | 110 ch. 1 CO, 754 al. 1 CO, 754 CO, 755 CO